HUBUNGAN RELIGIUSITAS, DUKUNGAN SOSIAL DAN TINGKAT STRES TERHADAP PERILAKU COPING ORANG TUA ANAK PENYANDANG DISABILITAS UNIT PELAYANAN DISABILITAS (UPD) KOTA TANGERANG SELATAN - Novian, Muhammad Nurman (Social Welfare Study Program, 2019)
Abstract. “Coping” behavior towards families of children with disabilities is suspected by a variety of parental conditions, such as the spiritual parent in dealing with social problems, parental stress levels and social support will trigger the direction of “coping” behavior of parents with children with disabilities. This study will look at the influence of spiritual variables, social support and stress levels in influencing the “coping” behavior of parents with children with disabilities who receive UPD Tangsel assistance. This research uses a quantitative approach. Based on the techniques in data collection, this research is a survey research. Survey research was carried out through questionnaires and formal interviews to collect information, background, behavior, beliefs and attitudes of people. Data processing was carried out using SPSS 25 software. At the value of the level of religiosity is smaller than α (0.005). So, 0,000 <0.005, then Ho is rejected and H1 is accepted. Thus, there is a relationship between the level of religiosity with the level of coping. At the level of social support, the value is smaller than α (0.005). So, 0,000 <0.005, then Ho is rejected and H1 is accepted. In the stress level variable, the value is smaller than α (0.005). So, 0,000 <0.005, then Ho is rejected and H1 is accepted. The conclusion is that there is a relationship between the level of religiosity, the level of social support and the level of stress with the level of coping of parents of children with disabilities in the South Tangerang City Disability Service Unit (UPD). Abstrak. Perilaku coping terhadap keluarga anak penyandang disabilitas ditengarai oleh berbagai kondisi orang tua, seperti spiritual orangtua dalam menghadapi permasalahan sosialnya, tingkat stres orangtua dan dukungan sosialnya akan memicu arah perilaku coping orangtua dengan anak penyandang disabilitas. Penelitian ini akan melihat pengaruh dari variabel spiritual, dukungan sosial dan tingkat stres dalam mempengaruhi perilaku coping orangtua dengan anak penyandang disabilitas penerima bantuan UPD Tangsel. Penelitian ini menggunakan pendekatan kuantitatif, berdasarkan teknik dalam pengambilan datanya maka penelitian ini merupakan penelitian survei. Penelitian survei dilakukan melalui kuesioner tertulis serta wawancara formal guna mengumpulkan informasi, latar belakang, perilaku, kepercayaan dan sikap orang, pengolahan data dilakukan menggunakan software SPSS 25. Pada nilai tingkat religiusitas lebih kecil dari α (0,005). Sehingga 0,000 < 0,005, maka Ho ditolak dan H1 diterima. Dengan demikian terdapat hubungan tingkat religiusitas dengan tingkat coping. Pada tingkat dukungan sosial nilainya lebih kecil dari α (0,005). Sehingga 0,000 < 0,005, maka Ho ditolak dan H1 diterima. Pada variabel tingkat stress nilainya lebih kecil dari α (0,005). Sehingga 0,000 < 0,005, maka Ho ditolak dan H1 diterima. Kesimpulannya yaitu terdapat hubungan antara tingkat religiusitas, tingkat dukungan sosial dan tingkat stress dengan tingkat coping orang tua anak penyandang disabilitas Unit Pelayanan Disabilitas (UPD) Kota Tangerang Selatan.